Framework for Measuring Knowledge Management for Service Development in Industrial Distributor - Sofianti, T D (Lecture notes in engineering and computer science, 2014)
Knowledge is asset to enhance the company's competitiveness. By managing knowledge, companies can improve performance in developing products and services to their customers. Many papers discuss the benefits, the process, and the success factors of knowledge management. However, discussion on its performance in B2B environment as a unitary system is still limited. Industrial distributors have customers at B2B level. It supports machines and equipments produced by manufactured by services. Industrial distributors sell the machines together with services to enhance value obtained by the customers from the machines. Services are provided starts from bidding process, ordering the machines from the manufacturer, delivery, installation, until the after sale stage such as maintenance. This paper promotes framework to measure knowledge management performance of industrial distributor in developing its service for the customers. The contribution of this paper is measurement framework of knowledge management in service development.